Proceedings of the 2021 5th International Seminar on Education, Management and Social Sciences (ISEMSS 2021) 2021
DOI: 10.2991/assehr.k.210806.006
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Fatigue Among Truck Drivers

Abstract: Fatigue is a significant dominating risk factor for transport workers, especially for long-distance truck drivers. Fatigued driving can easily lead to decreasing the drivers' judgment ability, slow reaction, and an increase of operational errors, and as well as increased probability of road traffic accidents. This study's aim is to identify the current evidence of risk factors contributing to fatigue for truck drivers. A literature search was made in 2021 and included articles back to the last ten years. All t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…According to the National Highway Traffic Safety Administration, around 100,000 police-reported drowsy-driving crashes occur yearly in the United States, resulting in roughly 800 fatalities and approximately 50,000 injuries ( 3 ). As per official data from the United States, truck drivers are more prone to fatigue than other drivers in the 120,000 nationwide fatal and catastrophic traffic accidents, with driving fatigue accounting for 13% of truck incidents ( 4 ). In Malaysia, the Malaysian Institute of Road Safety Research (MIROS) found that fatigue is one of the leading causes of vehicle, truck, and bus accidents ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the National Highway Traffic Safety Administration, around 100,000 police-reported drowsy-driving crashes occur yearly in the United States, resulting in roughly 800 fatalities and approximately 50,000 injuries ( 3 ). As per official data from the United States, truck drivers are more prone to fatigue than other drivers in the 120,000 nationwide fatal and catastrophic traffic accidents, with driving fatigue accounting for 13% of truck incidents ( 4 ). In Malaysia, the Malaysian Institute of Road Safety Research (MIROS) found that fatigue is one of the leading causes of vehicle, truck, and bus accidents ( 5 ).…”
Section: Introductionmentioning
confidence: 99%